2019
DOI: 10.1038/s41598-019-49726-5
|View full text |Cite
|
Sign up to set email alerts
|

Multifractal and entropy analysis of resting-state electroencephalography reveals spatial organization in local dynamic functional connectivity

Abstract: Functional connectivity of the brain fluctuates even in resting-state condition. It has been reported recently that fluctuations of global functional network topology and those of individual connections between brain regions expressed multifractal scaling. To expand on these findings, in this study we investigated if multifractality was indeed an inherent property of dynamic functional connectivity (DFC) on the regional level as well. Furthermore, we explored if local DFC showed region-specific differences in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 87 publications
(146 reference statements)
1
34
0
Order By: Relevance
“…The rightful question arises of how the performance of entropy-related measures could be affected by the presence of long-range correlations. In an earlier study we found that regions with stronger autocorrelation expressed lower PE in their local FC dynamics and vice versa (Racz et al, 2019). However, according to Xiong et al (2017) this cannot be simply a consequence of long-range autocorrelation, as it only introduces a constant bias that is independent of the degree of autocorrelation.…”
Section: Multifractality and Temporal Complexity Of Dfc In Szmentioning
confidence: 80%
See 4 more Smart Citations
“…The rightful question arises of how the performance of entropy-related measures could be affected by the presence of long-range correlations. In an earlier study we found that regions with stronger autocorrelation expressed lower PE in their local FC dynamics and vice versa (Racz et al, 2019). However, according to Xiong et al (2017) this cannot be simply a consequence of long-range autocorrelation, as it only introduces a constant bias that is independent of the degree of autocorrelation.…”
Section: Multifractality and Temporal Complexity Of Dfc In Szmentioning
confidence: 80%
“…Interestingly, in a subsequent study using the same dataset, the authors reported higher global SE in the SZ group that was later revealed to be the consequence of connections with higher SE in the visual recognition and auditory networks (Jia and Gu, 2019). These results may seem contradictory at first, nevertheless, in light of previous findings, they rather highlight the fact that FC dynamics vary greatly among brain regions (Racz et al, 2019) and that various regions could be affected in different ways in SZ. Our current results indicate a lower dynamical complexity of delta-band DFC in SZ.…”
Section: Multifractality and Temporal Complexity Of Dfc In Szmentioning
confidence: 82%
See 3 more Smart Citations